Review on Advance Catalyst for Biomass Gasification - Fona, Zahra; Irvan, Irvan; Tambun, Rondang; Fatimah, Fatimah; Setiawan, Adi; Adriana, Adriana (Applied Science and Engineering Progress, 2024)
The production of renewable energy from biomass waste is a recent innovative approach attracting significant attention. In this field, gasification technology has become an important method, enabling the transformation of biomass into bio-syngas for wide applications, such as electrical power, transportation fuel, cooking fuel, and chemicals. Bio-syngas containing hydrogen, carbon monoxide, carbon dioxide, and methane, are considered a clean and nontoxic fuel. To achieve an effective and efficient gasification process, capable of producing a fuel grade syngas, the use of the catalyst has been reported as the most practical approach. Although this concept is currently in development, it has captured the interest of numerous investigations. The current challenge is the development of a catalyst that can reduce tar, enhance H2 yield at a relatively low temperature, capture CO2, and maintain an extended active lifespan. Therefore, this research aimed to review the novel catalysts discussed in the latest literatures with the ability to produce the highest hydrogen product by using an effective process. The catalysts included natural minerals containing alkali metals, metals, carbon, and composites. Additionally, here also suggested the potential materials should be explored more intensively for gasification catalysts. This review would help to promote and accelerate the research and application of biomass gasification using local existing feedstock. Since the future of energy depended on renewable sources, producing syngas became one of the best options to support energy demand using biomass waste in Indonesia.